Computer Troubleshoots and Complaint Application - Zulkifli, Lokman Harith; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2022)
Computer Troubleshoots and Complaint Application is a mobile application that helps users to report problems and run computer troubleshoots. The situation of computer malfunctions and lack of skilled to solve them will interfere with daily activities. Also, the method of record the log is ineffective. Then, an application Computer Troubleshoot, and Complaint Application is built using the information system method. The Model Agile model is used as the methodology for the development of this application. The software used in the development of this application is Android Studio using JAVA and SQLite programming languages ​​as database data applications. This application will be used by employees of Bertam Properties Sdn Bhd. Application will be uses by employee and administrator. Among the functions of this application, the staff of can run a computer troubleshoot and make a complaint using the application. For administrators, complaint details will be sent to administrators and administrators can update the status of the complaint. Administrators can also add, edit, and search complaints that have been made by staff. It is hoped that this application is successfully developed and can provide the employee to make a complaint as well as a run a computer troubleshoots and help administrators manage their record more effectively